ANTI-INFLAMMATORY AND METABOLIC EFFECTS OF COFFEA CANEPHORA EXTRACT IN DIABETIC RATS: INSIGHTS FROM TNF-Α REDUCTION AND INSULIN SENSITIVITY INDICES - Siahaan, Jekson Martiar; Anto, Endy Juli; Fauzi, Tengku Muhammad; Pasaribu, Sumihar MR; Ginting, Hana Isal Salina; Sitorus, Friska Ernita; Hariati, Hariati; Fahdi, Firdaus; Ariani, Peny; Sujianto, Untung; Simanullang, Rostime Hermayerni; Sinurat, Suryati; et al. (African Journal of Infectious Diseases (AJID), 2025)
Background: Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder characterized by Insulin resistance, hyperglycemia, and systemic inflammation. Coffea canephora var. robusta contains bioactive compounds with potential antihyperglycemic and anti-inflammatory effects. This study aimed to evaluate the metabolic and inflammatory effects of its ethanolic extract in a rat model of T2DM. Materials and Methods: Forty-four male Wistar rats were randomized into 11 groups, including normal, diabetic controls, and treatment groups receiving ethanolic or ethyl acetate extracts (100–400 mg/kgBW). T2DM was induced using a high-fat diet and streptozotocin ± nicotinamide. Outcomes measured were fasting blood glucose (FBG), glucose-lowering percentage (%GL), fasting insulin resistance index (FIRI), quantitative insulin sensitivity check index (QUICKI), and TNF-α levels. Results: The 400 mg/kgBW ethanolic extract group showed a significant reduction in FBG (p = 0.017), percentage of glucose lowering (p = 0.000), TNF-α levels (p = 0.000), and body weight (p = 0.000) compared to diabetic controls, indicating improved metabolic regulation. Conclusion: The ethanolic extract of C. canephora improves glycemic control, enhances insulin sensitivity, and reduces inflammation in T2DM rats, supporting its potential for future clinical validation.